2023
DOI: 10.1029/2022jg007051
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic Patterns of Sulfur in the Vegetation of the Tibetan Plateau

Abstract: Sulfur (S) plays an important role in plant growth and development. However, due to climatic conditions and limited data availability, the variation and allocation of S are largely unknown at regional or global scales. In this study, we systematically evaluated the S distribution patterns and storage in vegetation on the Tibetan Plateau for the first time, based on consistent field‐measured data of 2,040 plant communities. The mean S contents of leaves, branches, trunks, and roots were 1.68, 0.40, 0.19, and 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…At the regional scale, Dalle Fratte et al [12] measured 740 vascular plant species in northern Italy and reported LS as 2.1 mg g −1 . Terrestrial plants in China contained 1.58 mg g −1 (1900 species [27]), 1.55 mg g −1 (702 species [14]), 1.2 mg g −1 (348 species [50]), 2.13 mg g −1 (2207 species [15]) and 2.32 mg g −1 (2745 species [34]) LS, while in the Tibetan Plateau, the mean LS concentration was 1.68 mg g −1 at the community level (2040 communities [51]). We believed that the differences in the plant species they measured explained the variations in leaf S concentrations at the regional scales.…”
Section: Discussion (A) Global Ls Stoichiometry and The Relationships...mentioning
confidence: 93%
“…At the regional scale, Dalle Fratte et al [12] measured 740 vascular plant species in northern Italy and reported LS as 2.1 mg g −1 . Terrestrial plants in China contained 1.58 mg g −1 (1900 species [27]), 1.55 mg g −1 (702 species [14]), 1.2 mg g −1 (348 species [50]), 2.13 mg g −1 (2207 species [15]) and 2.32 mg g −1 (2745 species [34]) LS, while in the Tibetan Plateau, the mean LS concentration was 1.68 mg g −1 at the community level (2040 communities [51]). We believed that the differences in the plant species they measured explained the variations in leaf S concentrations at the regional scales.…”
Section: Discussion (A) Global Ls Stoichiometry and The Relationships...mentioning
confidence: 93%